2023
DOI: 10.1371/journal.pmed.1004237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating systematic targeted universal testing for tuberculosis in primary care clinics of South Africa: A cluster-randomized trial (The TUTT Trial)

Abstract: Background The World Health Organization (WHO) recommends systematic symptom screening for tuberculosis (TB). However, TB prevalence surveys suggest that this strategy does not identify millions of TB patients, globally. Undiagnosed or delayed diagnosis of TB contribute to TB transmission and exacerbate morbidity and mortality. We conducted a cluster-randomized trial of large urban and rural primary healthcare clinics in 3 provinces of South Africa to evaluate whether a novel intervention of targeted universal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…This supports Xpert Ultra’s use as part of recent efforts to move beyond symptom criteria in high burden settings. 25 Encouragingly, we did not observe drastically reduced Xpert Ultra specificity in contrast to previous research in our setting; however, this previous research was in self-reporting people with presumptive tuberculosis, who have a higher rate of previous tuberculosis than ART initiators without preselection based on symptoms. 22 …”
Section: Discussioncontrasting
confidence: 99%
“…This supports Xpert Ultra’s use as part of recent efforts to move beyond symptom criteria in high burden settings. 25 Encouragingly, we did not observe drastically reduced Xpert Ultra specificity in contrast to previous research in our setting; however, this previous research was in self-reporting people with presumptive tuberculosis, who have a higher rate of previous tuberculosis than ART initiators without preselection based on symptoms. 22 …”
Section: Discussioncontrasting
confidence: 99%
“…In 2021, WHO updated the recommendation that all PLHIV in high burden settings should get tested with molecular rapid diagnostic testing. More recently, novel approaches to TB testing among PLHIV, such as targeted universal testing for TB (TUTT) and computer-aided digital chest x-ray (DCXR-CAD), has been explored in high burden settings [18] , [19] . Since 2022, Zimbabwe, with the support from PEPFAR, has implemented the TUTT approach to optimize TB screening among PLHIV [20] .…”
Section: Discussionmentioning
confidence: 99%
“…With TUTT, everyone at a high risk of contracting TB receives a test [51]. A local study reported that TUTT identified more TB patients than the standard of care (20.7 patients with TB per clinic month versus 18.8, respectively) [52]. The NDOH reported a 17% increase in TB diagnosis in clinics with TUTT compared to the existing approach [50,51].…”
Section: Discussionmentioning
confidence: 99%